PENGARUH CAPITAL STRUCTURE, PROFITABILITY, FIRM SIZE, DAN LEVERAGE TERHADAP FIRM VALUE - Matthew, Christian; Hastuti, Rini Tri (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to examine the impact of capital structure, profitability, firm size, and leverage on firm value in consumer cyclicals sector companies listed on the IDX in 2019-2021. This study used a purposive sampling method and samples that fit the criteria were 74 companies. The data that has been collected is processed using E-Views 12. The literature indicates that capital structure has a negative significant effect on firm value, profitability and leverage have a positive insignificant effect on firm value and firm size has a negative and insignificant effect on firm value. This study concludes that capital structure, profitability, firm size, and leverage influence the decisions of company management, investors, and creditors.